The Effect of Timely Guarantees Based on Kafalah Bil Ujrah on Shopee on Customer Satisfaction - Dahlia, Iis; Hasan, Asyari (Budapest International Research and Critics University, 2025)
Customer trust is a critical element in ensuring operational continuity and success of a marketplace platform. Shopee, one of the largest marketplaces in Indonesia, strives to increase customer satisfaction through various innovative programs, one of which is the Timely Guarantees Program based on the kafalah bil ujrah. This study aims to analyze kafalah bil ujrah in the timely guarantees program at shopee to increase customer satisfaction and user confidence in the marketplace in terms of delivery accuracy. This study aims to analyze kafalah bil ujrah in the timely guarantees program at shopee to increase customer satisfaction and user confidence in the marketplace in terms of delivery accuracy. Data were collected through questionnaires distributed to 300 respondents who are active shopee users. This research uses a quantitative approach with a survey method. The results showed that the implementation of the timely guarantees program using the kafalah bil ujrah contract significantly affected customer satisfaction. With this warranty, customers feel safer and more confident in making transactions. Descriptive analysis shows that the majority of respondents are satisfied with the timely guarantees program implemented by shopee. The results of multiple linear regression tests state that the variables of the timely guarantees program (x1) and the kafalah bil ujrah contract (x2) significantly affect customer satisfaction (y). The novelty of this research is that the significance of these results reinforces the importance of the guarantee mechanism in increasing customer trust and satisfaction on e-commerce platforms. The benefits of research are that it can increase trust with a clear time guarantee and certainty in claim settlement can increase trust in the shopee platform and provide a better understanding of the kafalah bil ujrah contract (guarantee on the basis of ujrah or fee) which may not be widely known by customers and sellers.